Multi-objective optimization and analysis of a solar energy driven steam and autothermal combined reforming system with natural gas - Ishaq, H.; Dincer, I (ELSEVIER SCI LTD, 2019)
An Energetically Improved Steam-Autothermal Reforming (EISAR) novel concept is proposed in this study, and a novel idea to combine steam methane reforming with CO2 and steam based autothermal reforming is introduced for practical applications. A urea synthesis unit is also integrated with the proposed system to justify the idea of clean hydrogen production. The CO2 produced by the steam methane reforming is captured in CO2 based autothermal reforming and CO2 produced by the autothermal reforming is captured by urea synthesis system which converts CO2 into urea by reacting is with ammonia. According to the designed heat management of molten salt, electric power of 4 MW is produced by the steam Rankine cycle which is supplied to a community of 400 households. During the night time, the community of 400 households is fed to be provided with electricity through PEM fuel cell which utilities a part of hydrogen from the storage tank. Both Engineering Equation Solver (EES) and Aspen Plus software packages are employed for system simulation. Several sensitivity studies, cost and carbon emission analyses and multi-objective optimization studies are undertaken for the designed system. The energy and exergy efficiencies for the present are found to be 59.1% and 31.1%, respectively. Furthermore, the results of current analyses and optimization studies are presented and discussed accordingly.
Keywords: Natural gas; Solar heliostat field; Steam-autothermal methane reforming; Urea synthesis; CO2 capturing; Proton exchange membrane fuel cell; Efficiency; HYDROGEN-PRODUCTION; HEAT-RECOVERY; EXERGY; WIND; Energy & Fuels; Engineering